Determining the Place of "Muqaddamat-i-Abdul Haq" in Urdu Literature - un Nisa, Zeenat; Meu, Atta ur Rehman (sourcecoder, 2022)
This article aimed to determine the place of “Muqaddamat-i-Abdul Haq” in Urdu literature. For this purpose, different primary and secondary sources were consulted. The material obtained from the said sources was critically evaluated. As a result, “Muqaddamat-i-Abdul Haq” were found to serve as a milestone not only in upholding the Urdu treatise writing tradition, but also in the promotion of Urdu language. Therefore, “Muqaddamat-i-Abdul Haq” were concluded to be not just simple treatises (like many other formal treatises) but the forms of a great art ever produced in the world of Urdu literature.